A bivalent cyclic RGD-siRNA conjugate enhances the antitumor effect of apatinib via co-inhibiting VEGFR2 in non-small cell lung cancer xenografts - Lumin Liao; Bohong Cen; Guoxian Li; Yuanyi Wei; Zhen Wang; Wen Huang; Shuai He; Yawei Yuan; Aimin Ji (Taylor & Francis Group, 2021)
The vascular endothelial growth factor receptor 2 (VEGFR2) is considered to be a pivotal target for anti-tumor therapy against angiogenesis of non-small cell lung cancer (NSCLC). However, effective and low-toxicity targeted therapies to inhibit VEGFR2 are still lacking. Here, biRGD-siVEGFR2 conjugate comprising murine VEGFR2 siRNA and [cyclo(Arg-Gly-Asp-D-Phe-Lys)-Ahx]2-Glu-PEG-MAL (biRGD) peptide which selectively binds to integrin αvβ3 receptors expressing on neovascularization endothelial cell was synthesized. The anti-tumor activity and renal toxicity of biRGD-siVEGFR2 or its combination therapy with low-dose apatinib were investigated on NSCLC xenografts. The immunogenicity of biRGD-siVEGFR2 was also evaluated in C57BL/6J mice. In vivo, intravenously injected biRGD-siVEGFR2 substantially inhibited NSCLC growth with a marked reduction of vessels and a down-regulation of VEGFR2 in tumor tissue. Furthermore, biRGD-siVEGFR2 in combination with low-dose apatinib achieved powerful anti-tumor effect with less nephrotoxicity compared with the regular dose of apatinib. Besides, no obvious immunogenicity of biRGD-siVEGFR2 was found. These findings demonstrate that biRGD-siVEGFR2 conjugate can be used as a new candidate for the treatment of NSCLC and its combination therapy with apatinib may also provide a novel strategy for cancer treatment in clinic.